2013
DOI: 10.4067/s0716-10182013000500002
|View full text |Cite
|
Sign up to set email alerts
|

Perfil etiológico y susceptibilidad antimicrobiana del primer episodio de infección urinaria febril

Abstract: The most common uropathogen was E. coli with good in vitro susceptibility to aminoglycosides and third generation cephalosporins, which are the recommended initial empirical therapy. E. coli ESBL-producing strains appear as emerging pathogens in community acquired UTIs in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
(18 reference statements)
1
0
0
1
Order By: Relevance
“…Similar findings from Tanzania reported that E. coli is the dominant organism as a cause of UTIs in children under-fives, and it is sensitive to fluoroquinolones and resistant to third- and fourth-generation cephalosporin’s (1). Similar studies were concluded in Marrakech [30] and in Kashmir (31) concluded that Escherichia coli were the most predominant isolate, followed by Klebsiellapneumoniae and Pseudomonas aeruginosa. However, they differ in the antibiotic sensitivity pattern, in Marrakech third generation cephalosporin’s and aminosides kept their effectiveness on the majority of isolates were the most effective treatment while, in the latter study, E. coli isolates were fully sensitive to ofloxacin, and cefuroxime.…”
Section: Discussionsupporting
confidence: 84%
“…Similar findings from Tanzania reported that E. coli is the dominant organism as a cause of UTIs in children under-fives, and it is sensitive to fluoroquinolones and resistant to third- and fourth-generation cephalosporin’s (1). Similar studies were concluded in Marrakech [30] and in Kashmir (31) concluded that Escherichia coli were the most predominant isolate, followed by Klebsiellapneumoniae and Pseudomonas aeruginosa. However, they differ in the antibiotic sensitivity pattern, in Marrakech third generation cephalosporin’s and aminosides kept their effectiveness on the majority of isolates were the most effective treatment while, in the latter study, E. coli isolates were fully sensitive to ofloxacin, and cefuroxime.…”
Section: Discussionsupporting
confidence: 84%
“…La infección del tracto urinario (ITU) es la segunda causa más frecuente de infección bacteriana en niños 1 . Su tratamiento inicial es frecuentemente empírico, por lo que la elección del antimicrobiano se basa en la epidemiología y patrones de susceptibilidad locales.…”
Section: Introductionunclassified